2007
DOI: 10.1002/app.26324
|View full text |Cite
|
Sign up to set email alerts
|

Keratin as a filler for carboxylated acrylonitrile‐butadiene rubber XNBR

Abstract: The presented investigations concern the distribution and characterization of keratin waste, derived from the processes of cattle skins, and its use as a filler for carboxylated acrylonitrile-butadiene rubber XNBR. The recovered keratin improves mechanical proprieties such as tensile strength, hardness, resistance to fuel and oil. The addition of keratin in a quantity of five parts per hundred rubber (XNBR) increases the crosslinking density of composites, as testified by the formed ion nodes and the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The authors ascribed these improvements to the formation of ionic bonds, and reinforcement in the covalent crosslinking since the keratin promotes mono-and disulfide bonds, which are more stable than the polysulfide bonds in standard vulcanizates. Moreover, they suggest that since the keratin filled composites have their water adsorption increased over time, also increasing electric conductance, they would be biodegradable after their use is expired (however, no biodegradability test was provided) [217]. They also observed similar results for systems with hair keratin and zinc oxide associated with styrene-butadiene rubber (SBR), describing improved resistance to thermooxidative aging, thermal and mechanical properties, and decreased flammability [218] and with nitrile-butadiene rubber and modified montmorillonite clay (MMC), observing increased water adsorption and thermal stability, and flammability decreased, proportionally, with increasing the keratin amount, while the mechanical properties were more dependent on the MMC amount [219].…”
Section: Butadiene Copolymer Rubbersmentioning
confidence: 99%
“…The authors ascribed these improvements to the formation of ionic bonds, and reinforcement in the covalent crosslinking since the keratin promotes mono-and disulfide bonds, which are more stable than the polysulfide bonds in standard vulcanizates. Moreover, they suggest that since the keratin filled composites have their water adsorption increased over time, also increasing electric conductance, they would be biodegradable after their use is expired (however, no biodegradability test was provided) [217]. They also observed similar results for systems with hair keratin and zinc oxide associated with styrene-butadiene rubber (SBR), describing improved resistance to thermooxidative aging, thermal and mechanical properties, and decreased flammability [218] and with nitrile-butadiene rubber and modified montmorillonite clay (MMC), observing increased water adsorption and thermal stability, and flammability decreased, proportionally, with increasing the keratin amount, while the mechanical properties were more dependent on the MMC amount [219].…”
Section: Butadiene Copolymer Rubbersmentioning
confidence: 99%
“…It has been shown that blending protein with zinc oxide provides for a decrease of particle size, which in turn provides for a better dispersion of the protein in the elastomeric matrix [12]. The blend was prepared by manually mixing powdered WPFF with zinc oxide in a 1 to 1 ratio.…”
Section: Characterizationmentioning
confidence: 99%
“…We deal with all kinds of biopolymers since 2002. The biopolimers which we are using in our investigations are keratin, collagen wastes of tanning industry, as well as bird feathers or potato protein which also are waste [5][6][7]. A small part of waste, from tannery or poultry industry, is used to produce, for example biogas or harmful animal feed.…”
Section: Introductionmentioning
confidence: 99%